Transcriptomic Analysis of Fuzi Lizhong Decoction for the Treatment of Stomach Ulcers. (21st February 2020) - Xin, Yang; Wang, Haijun; Xu, Lei
Abstract : This study aims to understand the treatment of stomach ulcers with FLD and to identify its potential target genes as well as related pathways by transcriptomic analysis. Rat stomach mRNA from a blank group (BG), a model group (MG), an untreated-model group (u-MG), and a treated group (TG) was sequenced. A partial least-squares discriminant analysis (PLS-DA) was used to differentiate the MG from the BG, and the Deseq2 R Package was used to identify differentially expressed genes between these groups. Furthermore, t -tests based on transcripts per million (TPM) were used to select different genes between MG and BG and significantly retrieved genes in TG, except for self-retrieved genes in u-MG. Finally, pathways regulated by retrieved genes were analyzed with KEGG database. Results showed that 327 of the 32, 623 total detected genes were different (p < 0.05 ) between the MG and BG. Among these genes, eighteen genes were significantly retrieved after rats were treated with FLD in TG, and they were considered as target genes on which FLD acted. In conclusion, FLD was deduced to cure stomach ulcers by affecting glycerolipid metabolism, fatty acid degradation, circadian entrainment, circadian rhythm, and dopaminergic synapse.